Fixing Leaks Assessing the Department of Defense's Approach to Preventing and Deterring Unauthorized Disclosures - Bruce, James B. (RAND Corporation, 2013)
In 2012, the Office of the Under Secretary of Defense for Intelligence established the Unauthorized Disclosures Program Implementation Team to prevent and deter the unauthorized disclosures of classified information by all Department of Defense personnel through the implementation of the UD Strategic Plan. RAND was asked to help monitor and assess the potential for effectiveness of this new initiative.